A comparison of WISC-IV test performance for Afrikaans, English and Xhosa speaking South African grade 7 learners - Van der Merwe, Adele (Rhodes University, Faculty of Humanities, Department of Psychology, 2008)
his study builds on South African cross-cultural research which demonstrated the importance of careful stratification of multicultural/multilingual normative samples for quality of education in respect of English and African language (predominantly Xhosa) speaking adults and children tested with the WAIS-III and WISC-IV, respectively. The aim of the present study was to produce an expanded set of preliminary comparative norms on the WISC-IV for white and coloured Afrikaans, white English and black Xhosa speaking Grade 7 children, aged 12 to 13 years, stratified for advantaged versus disadvantaged education. The results of this study replicate the findings of the prior South African cross-cultural studies in respect of quality of education, as groups with advantaged private/former Model C schooling outperformed those with disadvantaged former DET or HOR township schooling. Furthermore, a downward continuum of WISC-IV IQ test performance emerged as follows: 1) white English advantaged (high average), 2) white Afrikaans advantaged and black Xhosa advantaged (average), 3) coloured Afrikaans advantaged (below average), 4) black Xhosa disadvantaged (borderline), and 5) coloured Afrikaans disadvantaged (extremely low). The present study has demonstrated that while language and ethnic variables reveal subtle effects on IQ test performance, quality of education has the most significant effect "“ impacting significantly on verbal performance with this effect replicated in respect of the FSIQ. Therefore caution should be exercised in interpreting test results of individuals from different language/ethnic groups, and in particular those with disadvantaged schooling, as preliminary data suggest that these individuals achieve scores which are 20 "“ 35 points lower than the UK standardisation.
Keywords: Wechsler Intelligence Scale for Children; Wechsler Adult Intelligence Scale; Intelligence tests -- South Africa; Psychological tests -- Cross-cultural studies; Educational tests and measurements -- South Africa; Educational psychology -- South Africa; Language and languages -- Ability testing; Educational evaluation -- South Africa; Education, Elementary -- South Africa